The ultimate quotable Einstein - Einstein, Albert, 1879-1955 (Princeton University Press, 2011)
Here is the definitive new edition of the hugely popular collection of Einstein quotations that has sold tens of thousands of copies worldwide and been translated into twenty-five languages. The Ultimate Quotable Einstein features 400 additional quotes, bringing the total to roughly 1,600 in all. This ultimate edition includes new sections--"On and to Children," "On Race and Prejudice," and "Einstein's Verses: A Small Selection"--As well as a chronology of Einstein's life and accomplishments, Freeman Dyson's authoritative foreword, and new commentary by Alice Calaprice. In The Ultimate Quotabl.